Degradation of microplastics by formulated bacterial consortium isolated from mangrove areas in Peninsular Malaysia / Iffa Syamimi Rosli - Iffa Syamimi , Rosli (2017)
Regardless of its importance as an ecosystem, coastal mangroves have historically been favoured as dumping sites for numerous waste, including plastics. This study was aimed to investigate the ability of bacteria isolated from mangrove areas to degrade selected microplastics in laboratory condition. Physico-chemical parameters such as dissolve oxygen (DO), pH, temperature, salinity and biochemical oxygen demand (BOD) of water samples collected from mangrove areas were analyzed, to correlate with the microbial abundance in the areas. Potential degrading bacteria microbial consortium was inoculated in Bushnell Haas broth containing selected microplastics (sole carbon source). The medium was incubated in a shaker at 28°C for 30 days and the weight reduction of microplastics was recorded. In total, there are 38 species of bacteria isolated from mangroves sediment. It was found that microbial abundance at Matang Mangrove, Perak recorded the highest number of bacteria with 3.7 x 107 CFU/ml. Positive correlation was shown between microbial abundance with DO and BOD. After 30 days of exposure, polyethylene was reduced by 27.9%, polyethylene terephtalate by 24%, polypropylene by 19.5% and polystyrene by 15%. The change in the peak of FTIR confirmed the degradation potential of microplastics by these bacteria. The results revealed that the consortia isolated from mangrove sediment have the potential to degrade selected microplastic, thus can be used to bioremediate microplastics in a mangrove environment ecosystem.